Smart Plant Monitoring System Using LoRa Antenna - Ashari, Ezatun Nazirah; Xavier Ngu Toh Ik (Evolution in Electrical and Electronic Engineering, 2026)
Effective, long-range, low-power monitoring devices are required in smart agriculture to continuously monitor environmental conditions. This project works on designing a smart plant monitoring system using LoRa antenna technology for long-range communication. In this project, an ESP32 microcontroller is combined with temperature, humidity, and soil moisture sensors to acquire environmental data. To make it work in an independent outdoor setting, a solar-powered power supply system has been established. LoRa transceivers help in transmitting data from sensors to a receiver node for online monitoring. The results of this experiment confirm effective data transmission from sensors and reliable long-range communication. In the field of smart agriculture for plant monitoring, this proposed system offers an economical, power-efficient alternative.